Stratification in cognition and consciousness - Challis, Bradford H.; Velichkovskiĭ, B. M. (Boris Mitrofanovich) (Advances in consciousness research, 1999)
"The notion of stratification has played an important role in linguistics and evolutionary studies for some time, but its role in cognitive science has not yet been well articulated and identified. What is meant by stratification? What is the role and value of stratification in the contemporary study of cognition and consciousness? This collective volume speaks to these questions." "The volume presents stimulating and self-contained articles for researchers and students of experimental psychology and neuroscience, and is suitable for an advanced university course."--Jacket